2014
DOI: 10.1617/s11527-014-0369-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of FRC constitutive models to modelling of slabs

Abstract: Fibre reinforcement technology has advanced significantly in recent years and, as a result, expanded into different applications. In particular, steel fibre-reinforced concrete has been successfully employed in flat slabs of several buildings in Europe with fibres as the only reinforcement. However, design methods for fibre-reinforced concrete (FRC) structures do not consider differences that may result from material characterisation tests that are not representative of the structural behaviour and fibre orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 19 publications
2
19
1
3
Order By: Relevance
“…First of all, assuming an isotropic fiber orientation by considering an orientation factor equal to 1.0 is not suitable for the slabs tested, despite being common practice in the design. This was already reported by Blanco et al (2015b) and by Pujadas et al (2014a) for the case of the RILEM (RILEM 2003) and the Spanish recommendations (CPH 2008). Moreover, the flexural response of the small beam used in the characterization test is not representative of the structural behavior of slabs.…”
Section: Numerical Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…First of all, assuming an isotropic fiber orientation by considering an orientation factor equal to 1.0 is not suitable for the slabs tested, despite being common practice in the design. This was already reported by Blanco et al (2015b) and by Pujadas et al (2014a) for the case of the RILEM (RILEM 2003) and the Spanish recommendations (CPH 2008). Moreover, the flexural response of the small beam used in the characterization test is not representative of the structural behavior of slabs.…”
Section: Numerical Resultssupporting
confidence: 66%
“…Symmetry of the slabs was assumed in order to reduce the number of elements and the calculation time. Previous studies demonstrated that modeling a quarter of the slabs yields almost identical results to the ones obtained with the simulation of the whole slab (Blanco et al 2015b). The neoprene sheets located in the load application point and in the supports were also modeled to assure a realistic representation of the boundary conditions.…”
Section: Fig 6 Constitutive Diagram In Tension Used For the Simulatimentioning
confidence: 92%
“…Since the fibres tend to align perpendicularly to the cast direction and in the same plane of the concrete flow, the number of fibres crossing the failure plane increases. In line with that, a recent study by Blanco et al [7] revealed an enhanced sectional response in this type of element as the width increases.…”
Section: Introductionsupporting
confidence: 82%
“…The preliminary analysis showed that the P-d curves for the complete slab and for the quarter of the slab are practically identical. Based on such outcome [7], the reduced model was selected.…”
Section: Description Of the Fem Modelmentioning
confidence: 99%
“…Este aspecto ya ha sido probado a nivel experimental en dovelas [41] y losas [42][43][44] y cuantificado de forma cualitativa por [43][44][45][46]; asimismo, en [47,48] se han llevado a cabo simulaciones numéricas del comportamiento mecánico en losas de HRF, empleando distintas ecuaciones constitutivas, con el fin de poder calibrar dicho coeficiente. Sin embargo, pese a los avances en esta dirección, aún no se ha podido establecer un método sistemático y fiable para poder evaluar el coeficiente K para los distintos HRF y distintas condiciones de contorno.…”
Section: Parámetros De La Ecuación Constitutiva Para El Diseño De Hrfunclassified